Earthworm symbiont Verminephrobacter eiseniae mediates natural transformation within host egg capsules using type IV pili - Davidson, Seana K.; Dulla, Glenn F.; Go, Ruth A.; Stahl, David A.; Pinel, Nicolás (Frontiers in Microbiology, 2014)
The dense microbial communities commonly associated with plants and animals should offer many opportunities for horizontal gene transfer (HGT) through described mechanisms of DNA exchange including natural transformation. However, studies of the significance of natural transformation have focused primarily on pathogens. The study presented here demonstrates highly efficient DNA exchange by natural transformation in a common symbiont of earthworms. The obligate bacterial symbiont Verminephrobacter eiseniae is a member of a microbial consortium of the earthworm Eisenia fetida that is transmitted into the egg capsules to colonize the embryonic worms. In the study presented here, by testing for transformants under different conditions in culture, we demonstrate that V. eiseniae can incorporate free DNA from the environment, that competency is regulated by environmental factors, and that it is sequence specific. Mutations in the type IV pili of V. eiseniae resulted in loss of DNA uptake, implicating the type IV pilus (TFP) apparatus in DNA uptake. Furthermore, injection of DNA carrying antibiotic-resistance genes into egg capsules resulted in transformants within the capsule, demonstrating the relevance of DNA uptake within the earthworm system. The ability to take up species-specific DNA from the environment may explain the maintenance of the relatively large, intact genome of this long-associated obligate symbiont, and provides a mechanism for acquisition of foreign genes within the earthworm system.